2014
DOI: 10.3136/fstr.20.431
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Soybean Trypsin Inhibitor on the Generation of Oxygen Free Radical in Pancreas of Mice during Different Growth Periods

Abstract: The present study was undertaken to evaluate the effect of soybean trypsin inhibitor (STI) on the generation of oxygen free radical in pancreas of mice during different growth periods. Mice were divided into three groups and fed with different diets for 1, 2, 3, 4 and 5 weeks separately. The results showed that, MDA content of STI group was increased in the first two weeks, and its maximum appeared in the 3rd week, then it was dropped. Glutathione (GSH) content in serum and pancreas and total anti-oxidative ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The following candidate serum proteins were first selected based on their abundance in serum to illuminate them with our CTZ indicators: (i) human, bovine, and egg albumins (HAS, BSA, and OVA) were selected for the investigation, because they are the most abundant proteins in serum (35,000-52,000 mg/L) [15]; (ii) HIgG and BIgG were also selected, because they show the second-highest abundance among serum proteins (7000-16,000 mg/L); (iii) HTF was also chosen for the measurement, because it occupies the third abundant position among serum proteins (2000-3600 mg/mL); (iv) HγG and BγG were chosen, because γ-globulin grouping IgA, IgM, and IgY is the fourth abundant among serum proteins (i.e., 700-4000 mg/mL for IgA); (v) HFG was also selected, because it is the sixth abundant protein in serum; and (vi) STI and HFN were chosen for the measurement, because they are key components for the retardation of growth, digestive, and metabolic diseases [16] and human infective diseases [17], although they are the 19th and 26th abundant serum proteins, respectively.…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…The following candidate serum proteins were first selected based on their abundance in serum to illuminate them with our CTZ indicators: (i) human, bovine, and egg albumins (HAS, BSA, and OVA) were selected for the investigation, because they are the most abundant proteins in serum (35,000-52,000 mg/L) [15]; (ii) HIgG and BIgG were also selected, because they show the second-highest abundance among serum proteins (7000-16,000 mg/L); (iii) HTF was also chosen for the measurement, because it occupies the third abundant position among serum proteins (2000-3600 mg/mL); (iv) HγG and BγG were chosen, because γ-globulin grouping IgA, IgM, and IgY is the fourth abundant among serum proteins (i.e., 700-4000 mg/mL for IgA); (v) HFG was also selected, because it is the sixth abundant protein in serum; and (vi) STI and HFN were chosen for the measurement, because they are key components for the retardation of growth, digestive, and metabolic diseases [16] and human infective diseases [17], although they are the 19th and 26th abundant serum proteins, respectively.…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…It is not only a major source of ROS, but also the main target of ROS injury. The early studies indicated that STI could do harm to pancreas by increasing the formation of lipid peroxidation [11], but the mechanism remains unclear. So this paper aims to explore the effect of STI on the generation of free radicals in pancreatic mitochondria.…”
Section: Introductionmentioning
confidence: 99%